The Rhetoric of Sublime Astonishment in the Burkean and Blakean Readings of Milton - Antal, Éva (Hungarian Journal of English and American Studies, 2021)
Although the Lockean clear and distinct ideas greatly influenced Burke in his writing on the sublime, Milton’s impact is emphatically displayed in the dark and obscure rhetoric of the work. Despite the fact that Burke’s text abounds in classical quotations, it is Milton’s “strong expressions” that overpower the argument. William Blake also borrows a lot from Milton, but he radically rejects Burke’s ideas. Through the revelatory power of his visionary sublime, Blake overtly criticizes Locke’s shallow empiricism and Burke’s obscure rhetoric, arguing against a simple disparity of light/clarity versus darkness/obscurity. This essay explores the Burkean and the Blakean readings of the Miltonic sublime side by side, analyzing the Miltonic quotations in Burke’s A Philosophical Enquiry parallel with the verbal and visual references in Blake’s Milton, and highlighting the differences in their views.  (ÉA)